Veterinary and sanitary examination of rabbit meat: a comprehensive study on organoleptic, physicochemical, and microbiological parameters - Mendybayeva, E. R.; Atimbetova, A. A.; Oryntaev, K. B.; Kozhayeva, A. R. (ЗКАТУ им. Жангир хана, 2025)
In this work, a veterinary and sanitary examination of rabbit meat grown in the West Kazakhstan region was carried out. Three rabbits grown in the same conditions but different in age were selected for the study. The analysis included organoleptic, physicochemical and microbiological studies in order to assess the quality and safety of the products.Before slaughter, a veterinary examination of the animals was carried out, including an assessment of their general condition, activity, condition of the fur coat, mucous membranes and the presence of visible pathologies. According to the examination results, all three rabbits were clinically healthy: body temperature varied within 38.5–39.5 °C, breathing was uniform (50–60 respiratory movements per minute), heart rate was 130–160 beats per minute, mucous membranes were clean and pink, and the fur was smooth and shiny. No signs of infectious or parasitic diseases were detected. Organoleptic analysis showed that all samples met the standards for fresh meat: they were pale pink, had a dense consistency and a specific smell. Physicochemical studies revealed a pH in the range of 5.7–6.2, which indicates good meat quality. The reaction to peroxidase was positive, indicating the freshness of the product. Determination ofammonia and ammonium salts showed their absence, which indicates proper storage and no signs of decomposition.Microbiological analysis confirmed that the meat meets sanitary requirements: pathogenic microorganisms, including E. coli and salmonella, were not detected. In one sample, single cocci and gram-positive bacilli were detected, but their number did not exceed the permissible norms.Comparative analysis showed that differences in meat quality are due to the age of the animals. Samples from younger rabbits had higher moisture content and a tender consistency, while meat from older animals had a denser structure and a higher dry matter content. The results of the study confirmed that rabbit meat has high nutritional and sanitary-hygienic characteristics. It is safe for consumption and meets established quality standards. The data obtained emphasize the importance of monitoring the conditions of keeping, feeding and slaughtering animals to ensure stable product quality. В данной статье проведена ветеринарно-санитарная экспертиза мяса кролика, выращенного в Западно-Казахстанской области. Для исследования было отобрано три кролика, выращенных в одинаковых условиях, но различавшихся по возрасту. Анализ включал органолептические, физико-химические и микробиологические исследования с целью оценки качества и безопасности продукции.Результаты исследования подтвердили, что мясо кролика обладает высокими пищевыми и санитарно-гигиеническими характеристиками. Оно является безопасным для потребления и соответствует установленным стандартам качества. Полученные данные подчеркивают важность контроля условий содержания, кормления и забоя животных для обеспечения стабильного качества продукции.
Veterinary and sanitary examination of rabbit meat: a comprehensive study on organoleptic, physicochemical, and microbiological parameters / E. R. Mendybayeva, A. A. Atimbetova, K. B. Oryntaev, A. R. Kozhayeva. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2025. - № 1-1 (78). Iss. І. - Р. 215-224 (Uralsk). - ISSN 2305-9397
Keywords: veterinary sanitary expertise; domestic rabbit; physicochemical research; pre-slaughter inspection; organoleptic research; журнал кокснво; научный журнал; зко; ЗКАТУ